Re-imagining cultural studies : the promise of cultural materialism - Milner, Andrew (Sage, 2002)
Re-imagining Cultural Studies restores Williams to a central position in relation to the formation and development of cultural studies. The book is a much-needed reappraisal of the Williams approach, correcting misinterpretations and demonstrating its singular relevance to the problems and potentials facing cultural studies today.
Keywords: Williams, Raymond -- Political and social views.; Williams, Raymond; Social evolution.; Historical materialism.; Culture.; Cultural Evolution; Évolution sociale.; Matérialisme historique.; SOCIAL SCIENCE -- Anthropology -- Cultural.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Popular Culture.; Culture; Historical materialism; Political and social views; Social evolution; Kulturtheorie; Kulturwissenschaften; Cultuurfilosofie.; Culturele studies.; Marxisme.; Cultural studies -- Philosophie.; Kulturtheorie.